British pharmacopoeia 2004 (Addendum 2005 electronic) - British Pharmacopoeia Commission; Great Britain. Dept. of Health (London : Stationery Office, 2004)
Fully searchable CD-ROM comprising British pharmacopoeia 2004, British pharmacopoeia (veterinary) 2004, British approved names 2002.
Title from disc label.
'Incorporating the requirements of the 4th edition of the European Pharmacopoeia 2002 as amended by supplements 4.1 - 4.8 inclusive :-case cover.
Updates and other added value services available through the Internet.
System requirements: PC; Windows 95/98/2000/NT4.0; 486 or higher processor; 8MB RAM or higher; 10MB hard disk capacity (standard installation); SVGA display adaptor at 640x480, minimum 256 colours; double speed CD-ROM drive or faster.
Keywords: Pharmacopoeias -- United Kingdom